Membangun Kewaspadaan Publik: Sosialisasi Anti-Hoaks Pemilu Melalui Brosur Sebagai Taktik Edukasi Yang Efektif - Wolon, Frederikus; Putri, Putu Indah Dianti (LPPM Universitas HKBP Nommensen, 2024)
In the 2024 General Election, Indonesians will use their voting rights to elect five political positions, namely the president and vice president, members of the DPR, members of the DPD, members of the provincial DPRD and members of the district / city DPRD in accordance with Law Number 7 Year 2017. The activity of building public awareness with anti-hoax socialization through brochures ahead of the election was held in Padangsambian Klod Village, West Denpasar District, Denpasar City, Bali Province. With the massive socialization of anti-hoax through brochures in Padangsambian Klod Village, it is hoped that the community will be more vigilant and not easily provoked by SARA (ethnicity, religion, race, and intergroup) issues or misleading information spread by irresponsible individuals. This community service activity uses the participatory Action Research (PAR) method. The data collection method used in this research is observation, brochure distribution, and documentation. intergroup) or misleading information spread by irresponsible people. The purpose of this community service activity is to increase public awareness of hoax news on social media related to elections. to increase public awareness of hoax news on social media related to elections. The author hopes that in the future the village community will not easily believe and spread information from sources that are not clear about the truth.